A Comparative Analysis of Thermoelectric Generator Type SP1848-27145 SA Using Three Circuit Variations - Maharani Putri (INFOKUM, 2025)
Thermoelectric generators (TEGs) are devices that convert heat energy into electrical energy based on the Seebeck effect. This study analyzes the performance of the SP1848-27145 SA thermoelectric generator using three different circuit configurations to determine the most efficient setup for power generation. The research evaluates the voltage, current, power output, and efficiency of each configuration under controlled temperature conditions. The experimental results indicate that different circuit arrangements significantly affect the power output of the thermoelectric generator. The series configuration produced the highest voltage output, while the parallel configuration generated a higher current. The hybrid configuration (a combination of series and parallel) provided a balance between voltage and current, resulting in optimal power efficiency. These findings contribute to the optimization of TEG applications in renewable energy systems, especially in low-power generation scenarios. Further studies could explore heat dissipation techniques and advanced materials to enhance thermoelectric efficiency.